The Effect Of Workload And Organizational Culture On Burnout With Work Stress As A Mediation Variable (Study On Employees Badan Penyelenggara Jaminan Sosial "Bpjs" Kesehatan Padang City - Wira Rizki Wirman; Laura Syahrul; Yulihasri (Jurnal Mantik, 2022)
The purpose of this research is to analyze the factors which cause employees to burnout in working, which include workload and organizational culture on burnout with work stress that employees feel as a mediation variable. Burnout is an important thing that must be considered by company management in managing company resources or employees. The population in this study are employees of Badan Peneyelenggara Jaminan Sosial BPJS Kesehatan Padang City, West Sumatera with a sample of 83 employees. The analytical method used descriptive statistical analysis and factor description analysis using SmartPLS 3.0. The result of this study shows that workload has a positive and significant effect on work stress; organizational culture has a negative and significant effect on work stress; workload, organizational culture, and work stress have a significant impact on burnout; work stress as a mediating variable has an effect on the workload on burnout and organizational culture on burnout.